Porous cup shape and installation mode influencing determinations of matric potential by tensiometers - Franco, Hélio Henrique Soares; Silva, Alvaro Pires da; Tormena, Cássio Antonio; Ferreira, Camila Jorge Bernabé; Nunes, Márcio Renato; Lima, Renato Paiva de; Libardi, Paulo Leonel (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to determine the measurement accuracy of the soil water matric potential (ψm) by puncture tensiometers with either rounded or pointed porous cups, installed with or without “soil mud”, and to compare the performance of these tensiometers with that of tensiometers equipped with mercury manometers. The experiment was conducted in a Ultisol, in a randomized complete block design, in a factorial arrangement with five replicates. Puncture tensiometers with rounded porous cups, installed with “soil mud”, present more elevated accuracy for ψm determination in a wider measurement range, resembling tensiometers equipped with mercury manometers in drying soil.